Application of a Terahertz System Combined with an X-Shaped Metamaterial Microfluidic Cartridge - Shih-Ting Huang; Shen-Fu Hsu; Kai-Yuan Tang; Ta-Jen Yen; Da-Jeng Yao (Micromachines, 2020)
Terahertz (THz) radiation has attracted wide attention for its ability to sense molecular structure and chemical matter because of a label-free molecular fingerprint and nondestructive properties. When it comes to molecular recognition with terahertz radiation, our attention goes first towards the absorption spectrum, which is beyond the far infrared region. To enhance the sensitivity for similar species, however, it is necessary to apply an artificially designed metamaterial sensor for detection, which confines an electromagnetic field in an extremely sub-wavelength space and hence receives an electromagnetic response through resonance. Once the resonance is caused through the interaction between the THz radiation and the metamaterial, a minute variation might be observed in the frequency domain. For a geometric structure of a metamaterial, a novel design called an X-shaped plasmonic sensor (XPS) can create a quadrupole resonance and lead to sensitivity greater than in the dipole mode. A microfluidic system is able to consume reagents in small volumes for detection, to diminish noise from the environment, and to concentrate the sample into detection spots. A microfluidic device integrated with an X-shaped plasmonic sensor might thus achieve an effective and highly sensitive detection cartridge. Our tests involved not only measurements of liquid samples, but also the performance of a dry bio-sample coated on an XPS.